2021
DOI: 10.3390/microorganisms9071509
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Cellular Interactors of the Endogenous Retrovirus-K Integrase Enzyme

Abstract: Integrase (IN) enzymes are found in all retroviruses and are crucial in the retroviral integration process. Many studies have revealed how exogenous IN enzymes, such as the human immunodeficiency virus (HIV) IN, contribute to altered cellular function. However, the same consideration has not been given to viral IN originating from symbionts within our own DNA. Endogenous retrovirus-K (ERVK) is pathologically associated with neurological and inflammatory diseases along with several cancers. The ERVK IN interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 152 publications
1
5
0
Order By: Relevance
“…In addition, only ERVK PR contained an Nterminal SxIP motif (Figure 1, aa. 80-94) that binds to EBH domains in end-binding proteins involved in microtubule transport (56), similar to what is predicted for ERVK integrase (57). This pattern of consistent SxIP motifs in ERVK proteins may point to a unique usage of microtubule networks through EBH domain interaction.…”
Section: Characterization Of Eukaryotic Linear Motifs In Ervk Proteas...supporting
confidence: 56%
See 1 more Smart Citation
“…In addition, only ERVK PR contained an Nterminal SxIP motif (Figure 1, aa. 80-94) that binds to EBH domains in end-binding proteins involved in microtubule transport (56), similar to what is predicted for ERVK integrase (57). This pattern of consistent SxIP motifs in ERVK proteins may point to a unique usage of microtubule networks through EBH domain interaction.…”
Section: Characterization Of Eukaryotic Linear Motifs In Ervk Proteas...supporting
confidence: 56%
“…80-94) for binding to EBH domains in end-binding proteins involved in microtubule transport (56). Of note, ERVK IN is also predicted to interact with end-binding proteins (57), and the same SxIP motif (ELME000254) is found in both ERVK enzymes. The cluster related to the plus-end tracking proteins (+TIP) consist of only microtubule associated protein RP/EB family members (MAPRE1, MAPRE2, and MAPRE3) and the microtubule motor protein kinesin family member 14 (KIF14), making it by far the smallest grouping within the ERVK PR interactome (Figure 3).…”
Section: Ervk Protease May Preferentially Use End-binding Protein-bas...mentioning
confidence: 99%
“…However, the REEAD analysis performed showed that no viruses with active integrase can be detected in the cell culture supernatant. Integrase enzymes are found in all retroviruses and are highly crucial for the process of viral integration into host DNA and virion maturation [67]. The finding that our MLV-specific integrase probes were unable to detect MLV-integrase in supernatants of cultured GRX cells might indicate that the produced viral particles strongly adhere to the surface of the cells.…”
Section: Discussionmentioning
confidence: 86%
“…For example, HERV-K (HML-2) integrase binds to a protein called TRIM28, which is involved in gene silencing and DNA repair. This interaction may help HERV-K (HML-2) evade host defense mechanisms and increase its integration efficiency [137].…”
Section: Potential Use Of Antiviral Drugsmentioning
confidence: 99%